Sovereignty, Nationalism, and the Quest for Homogeneity in Interwar Europe - Dalle Mulle, Emmanuel 1985- HerausgeberIn; Rodogno, Davide 1972- HerausgeberIn; Bieling, Mona HerausgeberIn (Bloomsbury Academic, 2023)
Interwar European minority questions have been predominantly discussed in the context of Eastern Europe until now. This open access book challenges that geographical emphasis by examining both Eastern and Western European experiences. It thus lays the foundation for a new comparative international history of the relations between national majorities and minorities in Europe after the Great War. Building on the assumption that nationalist conflicts are based on dynamic interactions between multiple actors, this book brings together different perspectives and methodological approaches (political, social and transnational) to provide a comprehensive account of minority questions between the two World Wars. With contributions from leading academics and emerging scholars based in Austria, Ireland, Poland, Spain, Switzerland, the UK and the USA among others, Sovereignty, Nationalism, and the Quest for Homogeneity in Interwar Europe is a wide-ranging study which is firmly anchored in the history of the transition from empires to nation-states as well as in the history of human rights and the nation-state. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Swiss National Science Foundation (SNSF)